The Performance of the Turjagwali Unit of the Traffic Police of Polresta Pati through Patrols in Preventing Traffic Accidents in Blackspot Zones to Achieve Traffic Security, Safety, Order, and Smoothness. - Muhammad Alif Zhafar Ghali (Tanggon Kosala, 2023)
In 2021 according to the calculations of the Central Statistics Agency, Indonesia will experience a population increase of 1.13% with a total of 275,770,000 people. This increase was accompanied by an increase in the economy and community needs, so that the mobility carried out by the community was increasing. To support this mobility, people use transportation. The more transportation people use, the number of traffic violations and accidents also increases. This study aims to analyze the performance of the Turjagwali Sat Traffic Unit of the Pati Police in preventing traffic accidents in the blackspot zone through patrols. In writing this final assignment, the author uses concepts and theories which are used as an analytical knife for discussing the problems found and providing problem solving for the Turjagwali Satlantas Polresta Pati Unit. From the results of research conducted by the author, many factual conditions in the implementation of patrols by the Turjagwali Satlantas Polresta Pati Unit are not in accordance with the rules, namely Perkabaharkam No. 1 of 2017 concerning Patrols. This discrepancy was influenced by both internal and external factors so that during the implementation of the patrol there were many obstacles and problems faced by the Pati Polresta Polresta Turjagwali Unit. The implementation of patrols to prevent traffic accidents in the blackspot zone by the Turjagwali Satlantas Unit of the Pati Police is expected to comply with the rules in carrying out tasks and remain guided by Law no. 2 of 2002 concerning the National Police and Law no. 22 of 2009 concerning Road Traffic and Transportation. Therefore, the author provides several problem solving discussed in this final project. In the end, the authors can conclude that the performance of the Turjagwali Satlantas Polresta Pati Unit through patrols in preventing traffic accidents in the blackspot zone is not optimal. Problem solving and suggestions provided by the authors discussed in this final project are expected to have a positive influence on the implementation of patrols by the Turjagwali Unit so that traffic accidents in the blackspot zone can be reduced and the realization of traffic monitoring in the jurisdiction of the Pati Police.